Today I feel silly : & other moods that make my day - Curtis, Jamie Lee ([s.l.] : HarperCollins Publishers, 1998)
A child's emotions range from silliness to anger to excitement, coloring and changing each day.
"Joanna Cotler books"
Keywords: Emotion-Fiction; Stories in rhyme